International cooperation in disaster risk reduction in the region of South Eastern Europe - Kešetović, Želimir (Napredak, 2025)
Different kinds of natural and anthropogenic disasters are increasingly numerous in modern “risk society”, while their consequences are larger and larger, often exceeding the possibilities of responding to them not only at the local, but also at the national level. All this calls for various forms of international cooperation in disaster risk reduction and emergency management. Apart from global organizations, an important role in disaster risk reduction is also played by institutional organizational forms in the EU and some of its regions. In the region of South Eastern Europe, generally prone to crises, there is only one regional initiative – Disaster Preparedness and Prevention Initiative (DPPI) and International Sava River Basin Commission (Sava Commission). It is certainly both necessary and possible to improve the existing institutional arrangements and to devise other ones to raise the capacities of these countries for disaster risk management.
Keywords: disasters; international cooperation; region of South Eastern Europe; DPPI; Sava Commission